Acinetobacter baumannii in the critically ill: complex infections get complicated - Cavallo, Ilaria; Oliva, Alessandra; Pages, Rebecca; Sivori, Francesca; Truglio, Mauro; Fabrizio, Giorgia; Pasqua, Martina; Pimpinelli, Fulvia; Di Domenico, Enea Gino (Frontiers in Microbiology, 2023)
Acinetobacter baumannii is increasingly associated with various epidemics, representing a serious concern due to the broad level of antimicrobial resistance and clinical manifestations. During the last decades, A. baumannii has emerged as a major pathogen in vulnerable and critically ill patients. Bacteremia, pneumonia, urinary tract, and skin and soft tissue infections are the most common presentations of A. baumannii, with attributable mortality rates approaching 35%. Carbapenems have been considered the first choice to treat A. baumannii infections. However, due to the widespread prevalence of carbapenem-resistant A. baumannii (CRAB), colistin represents the main therapeutic option, while the role of the new siderophore cephalosporin cefiderocol still needs to be ascertained. Furthermore, high clinical failure rates have been reported for colistin monotherapy when used to treat CRAB infections. Thus, the most effective antibiotic combination remains disputed. In addition to its ability to develop antibiotic resistance, A. baumannii is also known to form biofilm on medical devices, including central venous catheters or endotracheal tubes. Thus, the worrisome spread of biofilm-producing strains in multidrug-resistant populations of A. baumannii poses a significant treatment challenge. This review provides an updated account of antimicrobial resistance patterns and biofilm-mediated tolerance in A. baumannii infections with a special focus on fragile and critically ill patients.